2005
DOI: 10.1038/sj.cr.7290343
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vitro system for gamete fusion in maize

Abstract: Various systems by using electric pulse, calcium, or polyethylene glycol have been developed in the past decade for the in vitro fusion of plant gametes. These in vitro systems provide a new way to study the fertilization mechanisms of plants. In this study, we developed a bovine serum albumin (BSA)-mediated fusion system for the in vitro fusion of maize gametes. The in vitro fusion of the isolated single egg cell and sperm cell of maize was observed microscopically in the BSA solution and the fertilized egg c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Although the technique could be used for detecting calcium in female sex cells during fertilization, a high background concentration of calcium is unavoidable, which makes it difficult to recognize the specific signals triggered by gamete fusion. We recently reported a novel procedure for IVF through which gamete fusion can be carried out in the medium without exogenous calcium (Peng et al 2005). We proposed that this procedure might simplify the investigation of the detection of calcium changes during fertilization by eliminating possible artifacts resulting from exogenous calcium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the technique could be used for detecting calcium in female sex cells during fertilization, a high background concentration of calcium is unavoidable, which makes it difficult to recognize the specific signals triggered by gamete fusion. We recently reported a novel procedure for IVF through which gamete fusion can be carried out in the medium without exogenous calcium (Peng et al 2005). We proposed that this procedure might simplify the investigation of the detection of calcium changes during fertilization by eliminating possible artifacts resulting from exogenous calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these types of stimulation also cause transient changes in [Ca 2+ ] cyt needs further investigation. We previously established an IVF system by polyethylene glycol (PEG)‐induced gamete fusion (Sun et al 2000), and more recently, we reported a new IVF technique with bovine serum albumin (BSA)‐induced gamete fusion (Peng et al 2005), which is believed to protect gamete viability and the membranes of the cells from possible damage by chemicals used for cell fusion. We therefore suggested that it could be a more suitable procedure for detecting calcium dynamic during fertilization, but the proposed advantage of the new technique needs to be confirmed.…”
mentioning
confidence: 99%
“…Egg cells of maize were isolated from ovules dissected from mature ears of maize as previously described by Peng et al . 13 . Half-ovules were incubated for 5 min at room temperature in an enzymatic solution containing 0.5% Macerozyme Onozuka R10 (Yakult Honsha, Tokyo, Japan), 0.5% Cellulase Onozuka R10 (Yakult Honsha, Tokyo, Japan), 3 mM 2-(N-morpholino)-ethanesulfonic acid (MES), adjusted to 725 mOsmol/kg H 2 O with mannitol, pH 5.7.…”
Section: Methodsmentioning
confidence: 99%
“…The techniques for in vitro fertilization, which are known to be effective in the study of fertilization in animals and lower plants, put a light on the study of early events during and after fertilization in higher plants 10 . In vitro fertilization systems were established in maize, tobacco, white and rice 11 12 13 14 15 16 17 18 . Based on these systems, some important events during fertilization, such as differential fertilization, egg cell activation, block to polyspermy, have been investigated 19 20 21 22 23 24 25 .…”
mentioning
confidence: 99%
“…In vitro fertilization between isolated sperm and eggs has been achieved in rice and maize (Faure et al 1994;Kranz and Lorz 1994;Khalequzzaman and Haq 2005;Peng et al 2005), but not yet in Arabidopsis. Previous studies had established that in addition to its role in pollen tube guidance in Arabidopsis, HAP2 also was essential in seed formation at a step after deposition of sperm in the synergid cell in the general region of the egg (Johnson et al 2004;Mori et al 2006;von Besser et al 2006).…”
Section: Hap2 Is Not Required For Gamete Migration or Species-limitedmentioning
confidence: 99%